The effect of ICT use on the classroom management in English teaching - Daulay, Sholihatul Hamidah; Nabila, Afanin; Nasution, Ummi Aisah (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2024)
The use of information and communication technology (ICT) is reviewed in this article. Multimedia technology is just a teaching tool that may be utilized to improve the classroom experience; the concept of bringing multimedia into the classroom is not new. The purpose of this essay was to look at the perspectives and first-hand experiences of English language teachers on how ICT affects classroom management. A case study methodology, a subset of qualitative research design, was employed in this study. ICT is heavily used in management classroom training because teaching the development of a broad range of technical, social, and conceptual skills is necessary for management. English language instructors gain from the use of ICT since it improves instruction efficiency, inspires students to learn, and simplifies classroom operations.